Therapeutic Strategy in Low-Risk Papillary Thyroid Carcinoma – Long-Term Results of the First Single-Center Prospective Non-Randomized Trial Between 2011 and 2015 - Czarniecka, Agnieszka; Zeman, Marcin; Wozniak, Grzegorz; Maciejewski, Adam; Stobiecka, Ewa; Chmielik, Ewa; Oczko-Wojciechowska, Malgorzata; Krajewska, Jolanta; Handkiewicz-Junak, Daria; Jarzab, Barbara (Frontiers in Endocrinology, 2021)
Optimal therapeutic strategy in low advanced papillary thyroid carcinoma (PTC) is still a matter of debate. The management differs depending on the country. A prospective non-randomized study was performed to evaluate whether less extensive surgery could be a safe, acceptable and sufficient therapeutic option in PTC cT1N0M0 patients. The present paper summarizes the results of over a 5-year follow-up study. Material: Our prospective group (PG) treated between 2011 and 2015 consisted of 139 patients with cT1aN0M0 PTC who underwent lobectomy (LT) as initial surgical treatment (PGcT1aN0M0 group) and 102 cT1bN0M0 patients in whom total thyroidectomy (TT) with unilateral central neck dissection (CND) was performed (PGcT1bN0M0). PG was compared with the retrospective group (RG) of patients who underwent TT with bilateral CND between 2004 and 2006: 103 cT1aN0M0 patients (RGcT1aN0M0) and 91cT1bN0M0 (RGcT1bN0M0). The risks of reoperation, cancer relapse and postoperative complications were analyzed. Results: Only 12 cT1aN0M0 patients (7.6%) withdrew from the trial and underwent TT with bilateral CND. Over 90% of patients accepted less extensive surgery. In 4 cT1aN0M0 cases, TT with CND was performed due to lymph node metastases found intraoperatively. The initial clinical stage according to the TNM/AJCC 7th edition was confirmed histologically in 77% of cases in PGT1aN0M0 and in 72% in PGT1bN0M0, respectively. 24 PGcT1aN0M0 patients were reoperated on. In this group, cancer lesions in the postoperative histological specimens were found in 8 cases (32%). Five-year disease-free survival (DFS) was excellent and not statistically different between the prospective and retrospective groups (99.3% in PGcT1aN0M0 and 99.0%, in RGcT1aN0M0; p = 0.41 and 98%, in PGcT1bN0M0 and 94.4% in RGcT1bN0M0; p=0.19). No significant differences were observed in the incidence of early paresis of the recurrent laryngeal nerves between PG and RG. However, as predicted, LT completely eliminated the risk of postoperative hypoparathyroidism. Summary: The results of the prospective clinical confirm that less extensive surgery in adequately selected low-advanced PTC patients is both safe and sufficient.